(untitled) (SAARC Journal of Agriculture, 2025)
Bean pod borer, Maruca vitrata F. (Lepidoptera: Crambidae) is a destructive pest of country bean causing severe yield loss. Potency of novel formulated four insecticides were tested against M. vitrata on BARI Shim-5 following RCBD from November 2021 to February 2022. Four treatments with 3 doses viz., T1 = Cyproflanilide 10% DC (ACC-Cy), T2 = Profenofos 50%, T3 = Pyriproxyfen (Pyrifen 10.8 EC) and T4 = Noclaim 5 SG (Emamectin benzoate), and an untreated control were evaluated. All the treatments were found significantly effective against the pod borer over untreated control. The lowest number of pod borers were counted as 5.00, 3.33, 1.33 and 3.67 from Cyproflanilide 10% DC @ 0.60 mlL-1 of water while the highest as 14.00, 13.33, 15.00 and 14.67 from the untrated control at 1st, 5th, 10th and 15th days after treatments, respectively. The lowest (20.42g) infested pods plant-1 were harvested from Cyproflanilide 10% DC treated plants but the highest (86.26g) in the untreated control. The ranked of the treatments based on pod protection over control by number followed as Cyproflanilide 10% DC @ 0.60 ml L-1 of water > Pyriproxyfen @ 1.50 ml L-1 of water > Emamectin benzoate @ 1.25 g L-1 of water > Prophenophs 50% @ 0.75 ml L-1 of water. So, based on efficacy, Cyproflanilide 10% DC was found superior than Profenofos, Pyriproxyfen and Emamectin benzoate against M. vitrata. SAARC J. Agric., 23(1): 154-162 (2025)